Automation, skill requirements and labour-use strategies: high-wage and low-wage approaches to high-tech manufacturing in the automotive industry - Martin Krzywdzinski (New Technology, Work and Employment, 2017)
In light of debates about advanced manufacturing and concepts like Industrie 4.0, this article compares labour-use strategies in highly automated automotive supplier plants in a high-wage country (Germany) and a low-wage region (Central Eastern Europe). It shows considerable differences regarding skill requirements on the shop floor and the use of precarious employment contracts and examines three potential factors that explain them: national institutional frameworks, the power of employee representatives and the role of the plant within the companies and value chains. The analysis shows that the labour-use strategies depend less on process technologies per se, but rather on the institutional framework and the role of the factory in the rollout and ramp-up of new products and new process technologies. Such a role requires close cooperation between employees in the manufacturing areas and in product development, which in turn requires particularly high skills. The role of employee representatives in influencing labour-use strategies proves less important. The article uses quantitative data from a survey of employee representatives, as well as qualitative data from in-depth company case studies.
Keywords: 330; automation; skills; automotive industry; trade union; Industrie 4.0; temporary employment; technology; international division of labour